Insights into Surface Interactions between Metal Organic Frameworks and Gases during Transient Adsorption and Diffusion by In-Situ Small Angle X-ray Scattering - Ludovic F. Dumée; Li He; Peter Hodgson; Lingxue Kong (Membranes, 2016)
The fabrication of molecular gas sieving materials with specific affinities for a single gas species and able to store large quantities of materials at a low or atmospheric pressure is desperately required to reduce the adverse effects of coal and oil usage in carbon capture. Fundamental understanding of the dynamic adsorption of gas, the diffusion mechanisms across thin film membranes, and the impact of interfaces play a vital role in developing these materials. In this work, single gas permeation tests across micro-porous membrane materials, based on metal organic framework crystals grown on the surface of carbon nanotubes (ZiF-8@CNT), were performed for the first time in-situ at the Australian Synchrotron on the small angle X-ray scattering beamline in order to reveal molecular sieving mechanisms and gas adsorption within the material. The results show that specific chemi-sorption of CO2 across the ZiF-8 crystal lattices affected the morphology and unit cell parameters, while the sieving of other noble or noble like gases across the ZiF-8@CNT membranes was found to largely follow Knudsen diffusion. This work demonstrates for the first time a novel and effective technique to assess molecular diffusion at the nano-scale across sub-nano-porous materials by probing molecular flexibility across crystal lattice and single cell units.